All-cause mortality after ERCP - Kalaitzakis, Evangelos (Endoscopy, 2016)
Background and study aims: This study aimed to externally validate a recently developed English model for the prediction of 30-day mortality after endoscopic retrograde cholangiopancreatography (ERCP). Real-world mortality data beyond 30 days post-ERCP are scarce; thus, the study also aimed to develop a prediction model for mortality up to 12 months post-ERCP. Patients and methods: All patients who underwent their first ERCP during a 3-year period (n = 16 478), as identified from the Swedish Hospital Discharge Registry, were linked to the Swedish Death Registry. Factors associated with all-cause mortality up to 12 months post-ERCP were identified by Cox proportional hazards analysis. A prediction model was developed. Results: Post-ERCP mortality was 5 % at 30 days and increased to 11.9 % at 3 months. The English model slightly overpredicted 30-day mortality, which was corrected with recalibration. Discriminant validity of the recalibrated model was very good (c-statistic = 0.82). Independent predictors of medium-term mortality were: emergency admission (hazard ratio [HR] 1.48), cancer (HR 3.79), noncancer co-morbidity (1.33), gallstone-related diagnosis (HR 0.21), and age (HR 4.86 for ≥ 85 years vs. < 55 years). The c-statistic for 3 – 12-month mortality was 0.86 – 0.88. Specific ERCP complication codes were identified in 1.8 % of deaths within 30 days post-ERCP (0.09 % of ERCPs), and 75 % of deaths (18 % of ERCPs) within 1 year post-ERCP were due to cancer.Conclusions: Mortality doubled from 30 days to 3 months post-ERCP, but it was attributed mainly to underlying disease, notably cancer, and infrequently to ERCP-related causes. A previously developed model predicting 30-day mortality was externally validated. A model accurately predicting mortality up to 12 months post-ERCP was developed.